2019
DOI: 10.1016/j.heliyon.2019.e01359
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and protective role of Pulicaria undulata (L.) C.A. Mey. subsp. undulata against gastric ulcer induced by ethanol in rats

Abstract: Pulicaria undulata subsp. undulata (Family; Asteraceae) is a medicinal plant used to treat inflammation. The objective of this study is to explore the protective effect of the ethanol extract of P. undulata subsp. undulata aerial parts against ethanol induced gastric ulcer in rats. The chemical composition of plant extract, the unsaponifiable matter and the fatty acid methyl esters were analyzed. The biological evaluation was carried out through measuring ulcer indices, oxidative stress markers, certain marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Although it has been used in traditional medicine for a long time, it has become a topic of interest for medicinal research since the 1980s [ 16 ]. Previous studies have shown that P. crispa derivatives exert antioxidative [ 17 ], anti-inflammatory [ 18 ], and chemopreventive activities [ 19 ]. A phytochemical screening of P. crispa extract attributed these effects to the presence of coumarins, tannins, and flavonoids [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been used in traditional medicine for a long time, it has become a topic of interest for medicinal research since the 1980s [ 16 ]. Previous studies have shown that P. crispa derivatives exert antioxidative [ 17 ], anti-inflammatory [ 18 ], and chemopreventive activities [ 19 ]. A phytochemical screening of P. crispa extract attributed these effects to the presence of coumarins, tannins, and flavonoids [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, extracts from the Pulicaria species have been shown to inhibit neutrophil infiltration and alleviate oxidative stress. It was also postulated that it suppresses the generation of nitric oxide [ 27 ] and modulates the expression of intracellular adhesion molecule-1 (ICAM-1), tumor necrosis factor- (TNF-) α [ 18 ], and prostaglandin E2 [ 18 ]. Therefore, further study of their effects on the immune system, especially at the molecular level, will be particularly insightful.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of phenolic compounds, including flavonoids, seemingly plays a prominent role in the plant’s protection against oxidative stress in its saline habitat and, consequently, a strong antioxidant behavior is observed in the plant’s extract. These compounds are also reported to be beneficial as part of the extract in treating inflammatory disorders [ 35 ]. The LC-MS analysis also revealed the similarities in the presence of phytochemical constituents, to a certain extent, between the P. undulata , and other Pulicaria species (i.e., P. crispa and P. incisa ), which have shown presence of similar phenolics, and flavonoid contents (i.e., quercetin, kaempferol, and caffeic acid) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the presence of flavonoids and phenolic acids, sterols, and fatty acids are reported from several Pulicaria and other halophytic species [ 5 , 28 , 29 , 30 ]. Antioxidant and other physiological and hemostasis-related parameters—specifically in the context of soil, trace elements in the soil, generated salinity stress, habitat adaptation, and production and higher accumulation of phytoconstituents—have been found [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…et al,21 . Identification of active ingredient of PJ methanolic extract and its fractions was carried out by Al-Naqeb et al,12 , they have reported the presence of catechin-like compounds, mainly in the methanolic extract and its dichloromethane fraction and both have…”
mentioning
confidence: 96%